Revisiting the National Innovation System in Developing Countries - Maloney, William F. (World Bank, Washington, DC, 2017)
The paper argues that there is a greater commonality of approach between the National Innovation Systems approach and mainstream economic analysis than is often asserted, and that a better dialogue between the two could strengthen both perspectives. To this end, the paper uses an off-the-shelf neoclassical model to provide a tentative structure for what a National Innovation Systems schematic might look like and where its boundaries should be. Simulations from the model suggest how present benchmarking techniques may be misleading.